Patients with ankylosing spondylitis have been breast fed less often than healthy controls: a case–control retrospective study. Issue 5 (12th October 2015) - Montoya, J; Matta, N B; Suchon, P; Guzian, M C; Lambert, N C; Mattei, J P; Guis, S; Breban, M; Roudier, J; Balandraud, N
Abstract : Objective: Ankylosing spondylitis (AS) is a chronic inflammatory disease affecting the spine and pelvis of young adults. On the HLA-B27 genetic background, the occurrence of AS is influenced by the intestinal microbiota. The goal of our study was to test whether breast feeding, which influences microbiota, can prevent the development of AS. Methods: First, 203 patients with HLA-B27-positive AS fulfilling the modified New York criteria were recruited in the Department of Rheumatology, Ste Marguerite hospital in Marseilles. A total of 293 healthy siblings were also recruited to make up a control group within the same families. Second, 280 healthy controls, and 100 patients with rheumatoid arthritis and their siblings were recruited. The data collected were age, gender, number of brothers and sisters, age at disease onset, type and duration of feeding (breast or bottle). Results: Patients with AS had been breast fed less often than healthy controls. In families where children were breast fed, the patients with AS were less often breast fed than their healthy siblings (57% vs 72%), giving an OR for AS onset of 0.53 (95% CI (0.36 to 0.77), p value=0.0009). Breast feeding reduced familial prevalence of AS. The frequency of breast feeding was similar in the AS siblings and in the 280 unrelated controls. However, patients with AS were less often breast fed compared with the 280 unrelated controls (OR 0.6, 95% CI (0.42 to 0.89), p<0.01). Conclusions: Our study suggests a breastfeeding-induced protective effect on the occurrence of AS. To our knowledge, this is the first study of breastfeeding history in patients with AS.